Cigarette price variation around high schools: evidence from Washington DC. (January 2015) - Cantrell, Jennifer; Ganz, Ollie; Anesetti-Rothermel, Andrew; Harrell, Paul; Kreslake, Jennifer M.; Xiao, Haijun; Pearson, Jennifer L.; Vallone, Donna; Kirchner, Thomas R.
Abstract: This study examines lowest cigarette prices in all tobacco retail outlets in Washington D.C. ( n =750) in relation to the type and number of high schools nearby, controlling for confounders. The lowest overall and Newport menthol prices were significantly lower at outlets near public non-charter and charter schools compared with outlets near private schools. Given higher smoking prevalence and more price-sensitive youth subgroups in U.S. public schools, exposure to low prices may contribute to tobacco-related health disparities in minority and low-income populations. Tobacco taxes combined with policies to minimize the increasing use of price as a marketing tool are critical. Highlights: Youth are highly sensitive to cigarette prices, as are minority and low-income subgroups. Public schools have higher smoking prevalence and price-sensitive subgroups than private schools. Little is known about the distribution of cigarette prices in relation to schools and school type. The lowest prices in this study were significantly lower near public schools than private schools. Lower prices near public schools may contribute to tobacco-related disparities among youth.